S1PR4-dependent effects of Etrasimod on primary human myeloid immune cell activation - Sailer, Fiona K.; Palmer, Megan A.; Aliraj, Blerina; Heering, Jan; Brockmann, Andreas; Elewa, Mohammed A. F.; Röhrig, Aissa; Proschak, Ewgenij; Stepniak, Dariusz T.; Ramsey, Simeon; Brüne, Bernhard; Weigert, Andreas (Frontiers in Pharmacology, 2025)
BackgroundSphingosine-1-phosphate (S1P) and its five receptors S1PR1-5 play an essential role in the migration, differentiation and activation of various immune cells. Several S1PR modulators with distinct selectivity have been recently approved for the treatment of various inflammatory diseases. Among those are Ozanimod, an S1PR1/5 modulator approved for the treatment of ulcerative colitis and multiple sclerosis, and Etrasimod, an S1PR1/4/5 modulator approved for the treatment of ulcerative colitis. Chronic autoinflammatory diseases such as the inflammatory bowel diseases (IBDs) Crohn’s disease and ulcerative colitis are characterized by an abundance of disease-propagating immune cells in the gastrointestinal tract. Since currently available treatment options such as biologics provide a sometimes inadequate treatment response, one alternative strategy to treat IBDs is the use of S1P receptor modulators.ObjectiveWe aimed to investigate if targeting S1PR4 affects the impact of Etrasimod on the activation of primary human immune cells, and to elucidate the mode of action of Etrasimod on S1PR4.MethodsPrimary human macrophages, plasmacytoid dendritic cells and neutrophils were pretreated with S1P, Etrasimod (S1PR1/4/5), Ozanimod (S1PR1/5), Siponimod (S1PR1/5), CYM 50308 (S1PR4 agonist) and CYM 50358 (S1PR4 antagonist), and then stimulated with Zymosan A, ODN 2336 and PMA, respectively. We measured cytokine and chemokine production by macrophages and plasmacytoid dendritic cells via CBA/Legendplex, and survival and activation markers for neutrophils via flow cytometry. Confocal microscopy of S1PR-expressing CHO-K1 cell lines was used to study receptor internalization.ResultsWe found that signaling induced by S1P, Etrasimod and the S1PR4 agonist attenuates CCL20 and CXCL5 production by Zymosan-stimulated macrophages, and these findings were confirmed by S1PR4 knockdown. Additionally, S1PR4 was involved in the regulation of IFN-α production by ODN2336-stimulated plasmacytoid dendritic cells. Lastly, both Etrasimod and the S1PR4 agonist reduced the activation level of PMA-stimulated neutrophils. Regarding receptor dynamics, we show that Etrasimod induces internalization of S1PR4.ConclusionTaken together, our data show that S1PR4 takes on an essential role in the regulation of various immunological functions, and that Etrasimod can act as a superagonist/functional antagonist of S1PR4.